OP41 Facilitating Dialogue Of Real-World Evidence Use In Health Technology Assessment: Taxonomy Of Question/Data Source Pairings To Support A Registry Of Studies. (23rd December 2022) - Akehurst, Ron L; Murphy, Linda A; Mestre-Ferrandiz, Jorge; Solà-Morales, Oriol; de Pouvourville, Gérard; Cunningham, David; Corry, Sorcha; Franklin, Matthew; Chapman, Ann-Marie
Abstract : Introduction: This paper reports the results of the collaboration within the European initiative of new Reimbursement and aCCess Approaches (EUreccA) which is concerned with the use of real-world evidence (RWE) in health technology assessment (HTA) decision-making. The work grew from the observation of a large, very experienced group of HTA practitioners which found that the use of RWE varied depending on the type of question asked and the particulars of the data source(s) used. We set out to examine how RWE is used in HTA decision-making and to make proposals on its facilitation. Methods: Literature reviews covering earlier reviews of RWE use, academic papers, and HTA agency websites were combined with case studies involving interviews with decision-makers in four countries (England, France, Italy, Sweden) to identify the circumstances of breakdown of RWE use and to build a categorization of the uses of RWE and associated difficulties. This evidence supported the creation of a taxonomy of pairings of data sources and the questions they were used to address. The face validity of the approach was tested at an advisory board of senior HTA practitioners. Results: In total, 27 questions were identified and 10 types of data source, giving 270 pairings. These pairings were linked to relevant methods guidance and to examples of their use, itemizing HTA issues and decisions made. Reports are being prepared for publication, covering the detail of the methods of the literature searches; methods of the country case studies; a description of the taxonomy; and guidance on governance. Conclusions: When using RWE in HTA decision-making, the detail of the particular data sources and question addressed matter. Recently, both the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) and the Real-World Transparency Initiative have argued for a registry of the uses of RWE. The work described here offers a starting classification of the material that should be held in such a registry, and which in itself could be developed by the stakeholders, both agencies and companies, that use it, furthering trust and confidence.